The Relationship between Serum Ferritin and Insulin Resistance in Different Glucose Metabolism in Nonobese Han Adults - Bo-wei Liu; Xu-min Xuan; Jun-ru Liu; Fang-ning Li; Fu-Zai Yin (International Journal of Endocrinology)
The exact mechanism through which elevated serum ferritin promotes the development of type 2 diabetes is unknown. This study showed that ferritin concentration in impaired glucose regulation and newly diagnosed diabetes mellitus subjects of nonobesity already significantly increased when compared with normal glucose tolerant subjects of nonobesity. Elevated serum ferritin levels are associated with insulin resistance and may be not associated with the decline of insulin beta cells in different status of glucose tolerance in nonobese Han adults.